2017
DOI: 10.1007/s00464-017-5499-8
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal complications after robotic intersphincteric resection for low rectal cancer

Abstract: This is the first study reporting on the clinical outcomes of anorectal status after robotic ISR. Further studies are needed to assess the long-term effects of these anorectal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In this study, the robotic system was more commonly used for the treatment of total ISR, indicating that the robotic system could operate better in small spaces. The clinical outcomes were evaluated and reported to be safe in many studies, while anorectal complications, including oedematous haemorrhoids, anal stenosis, and neorectal mucosal prolapse, were more common after ISR ( 18 ). Regarding the oncological outcome, ISR showed comparable overall survival with APR for patients with low rectal cancer, especially for patients at stage I–II ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the robotic system was more commonly used for the treatment of total ISR, indicating that the robotic system could operate better in small spaces. The clinical outcomes were evaluated and reported to be safe in many studies, while anorectal complications, including oedematous haemorrhoids, anal stenosis, and neorectal mucosal prolapse, were more common after ISR ( 18 ). Regarding the oncological outcome, ISR showed comparable overall survival with APR for patients with low rectal cancer, especially for patients at stage I–II ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our cases were operated by minimally invasive surgery (MIS) (case 1, robot-assisted; case 2, laparoscope-assisted), which is the same to other previous studies in that most cases were treated by MIS [ 6 , 9 ]. Prolapse can happen with all types of ISR, but it is more common with total ISR.…”
Section: Discussionmentioning
confidence: 92%
“…Two cases in our study are not very old age considering common patient’s age of rectal cancer and rectal prolapse (case 1, 64 years old; case 2, 57 years old). Guraieb-Trueba et al [ 6 ] showed that the average age of patients is 65.6 years in their cohort study of neorectal mucosal prolapse (19 patients), while Kuo et al [ 9 ] reported 2 cases of average age 56.6 years. Based on reported cases, we noticed that it is common to occur in 5th and 6th decade.…”
Section: Discussionmentioning
confidence: 99%
“…In the study hospital, the treatment principle for CRC is to perform CCRT 6–8 weeks before surgery when the tumour is classified T3/4 and/or lymph node‐positive. The tumour is assessed using sigmoidoscopy at a distance of 3–5 cm from the anal verge, without external anal sphincter or levator ani muscle invasion (Kuo et al, ).…”
Section: Methodsmentioning
confidence: 99%